A Semantic Analysis of Living and Dead Metaphors in English Song Lyrics from Jungkook’s Golden Album - Riskiyani Amalia; Nine Febrie Novitasari; Dwi Taurina Mila Wardhani; Fadhl Mohammed Awadh Gharamah (English Department, Universitas Negeri Surabaya, 2025)
This study aims to explore and analyze the types and interpretations of metaphors found in songs from Jungkook’s Golden album. The analysis focuses on selected tracks including ‘3D’, ‘Seven - Explicit Version’, ‘Yes or No’, ‘Please Don’t Change’, ‘Somebody’, ‘Shot Glass of Tears’, ‘Closer to You’, ‘Standing Next to You’, ‘Hate You’, and ‘Too Sad to Dance’. Employing a qualitative research method, the study utilizes I.A. Richards’ (1936) framework to classify metaphor types and draws on the theories of Wittgenstein (2002) for interpreting metaphorical meanings. A total of ninety metaphorical expressions were identified, consisting of fifty-six living metaphors and thirty-four dead metaphors. Living metaphors were more frequently encountered, while dead metaphors appeared less often. The analysis reveals that living metaphors, due to their novelty and the introduction of unfamiliar expressions, tend to require deeper interpretation. In contrast, dead metaphors are more easily understood, as their repeated use over time has led to more conventional and simplified meanings.